Analisis Pengaruh Promo Voucher dan Kepuasan Konsumen terhadap Loyalitas Konsumen Tokopedia - Is Fadhillah; Alexander Mico Ray Themasoa (Yayasan Literasi Sains Indonesia, 2025)
Currently, the development of information technology is very complex and has many impacts on human life, including business on the internet, namely E-Commerce which saves time and does not require large capital promote products. One of them is the Tokopedia website which sells goods and services anyone can do business and compete with low costs. This website provides business and selling opportunities various products at more affordable prices than general stores. To launch marketing, Tokopedia collaborates with banking institutions and other companies to make it easier for consumers to do payment. This study aims to find out whether Promos and Consumer Satisfaction Affect Tokopedia Consumer Loyalty Results The number of respondents The questionnaire in this study was 100 respondents. The type of research used by researchers is using quantitative research methods and the technique used in this research is using simple linear regression analysis. The results of the research that have been examined by researchers are as follows based on the results of statistical testing on the results of the T test based on the data output from the results of statistical tests showing Tokopedia Consumers has a significant effect on Loyalty to Tokopedia seen from the calculation of t-count 6,383> t-table 2,371 with a significance of 0.000.